2009
DOI: 10.1038/sj.bjc.6605095
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sub-acute changes in cardiac function after cisplatin-based combination chemotherapy for testicular cancer

Abstract: Long-term cardiovascular morbidity is increasingly observed in chemotherapy-treated testicular cancer survivors, but little is known of early sub-clinical changes in cardiac function. We prospectively evaluated cardiac function in testicular cancer patients by echocardiography. Systolic (Wall Motion Score Index) and diastolic (E/A-ratio and Tissue Velocity Imaging (TVI)) parameters, and serum levels of N-Terminal pro-Brain Natriuretic Peptide (NT-proBNP) were assessed before the start of chemotherapy and 1 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
3
20
0
2
Order By: Relevance
“…These observations suggest that there is no completely "safe" dose of anthracyclines in children (Barry et al, 2007) or adults (Menna et al, 2012). In other studies, the risk of delayed MI correlated with patient's exposure to alkylators like platinum (Altena et al, 2009) or tubulin-active agents like vincristine (Swerdlow et al, 2007). These findings denote that with current treatment protocols, anthracyclines and nonanthacycline chemotherapeutics are life-saving but introduce a lifetime risk of cardiac events.…”
Section: General Concepts On Cardiotoxicity From Antitumor Drugsmentioning
confidence: 73%
See 1 more Smart Citation
“…These observations suggest that there is no completely "safe" dose of anthracyclines in children (Barry et al, 2007) or adults (Menna et al, 2012). In other studies, the risk of delayed MI correlated with patient's exposure to alkylators like platinum (Altena et al, 2009) or tubulin-active agents like vincristine (Swerdlow et al, 2007). These findings denote that with current treatment protocols, anthracyclines and nonanthacycline chemotherapeutics are life-saving but introduce a lifetime risk of cardiac events.…”
Section: General Concepts On Cardiotoxicity From Antitumor Drugsmentioning
confidence: 73%
“…Asymptomatic cancer survivors often present echocardiographic indices of diastolic dysfunction characterized by altered relaxation or restrictive pattern (stiffness) (Carver et al, 2007;Altena et al, 2009). In nononcologic settings, persistent altered relaxation or stiffness cause left ventricle (LV) remodeling that makes diastolic dysfunction progress to HF with preserved left ventricle ejection (LVEF) and eventually to HF with reduced LVEF (Borlaug and Paulus, 2011).…”
Section: General Concepts On Cardiotoxicity From Antitumor Drugsmentioning
confidence: 99%
“…Esophageal cancer patients generally have a number of risk factors for ischemic heart disease, including older age, histories of tobacco use and/or obesity [23]. All patients were irradiated combined with chemotherapy, most often with cisplatinum and 5-FU, which are both associated with increased risks of thrombus formation [24][25][26]. Based on the available data, it was impossible to correct for these potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported a worsening of the diastolic cardiac function few months after cisplatin-based chemotherapy compared with initial diastolic function [59,60]. In line with this, a longitudinal study reported a gradual decline in diastolic cardiac function in long-term TCSs treated with cisplatin-based chemotherapy, with hypertension and obesity being associated with larger declines in diastolic parameters [61].…”
Section: Cardiovascular Risk Factors and Endothelial Dysfunctionmentioning
confidence: 82%